2015
DOI: 10.1016/j.amjcard.2015.01.539
|View full text |Cite
|
Sign up to set email alerts
|

Factors Driving Anticoagulant Selection in Patients With Atrial Fibrillation in the United States

Abstract: With the introduction of novel oral anticoagulants (NOACs), the factors driving anticoagulant selection in atrial fibrillation (AF) in real-world practice are unclear. The goal was to examine whether and to what extent utilization has been driven by predictions of stroke risk (treatment benefit), bleeding risk (treatment harm), or prescription benefits’ coverage. We extracted a cohort of non-valvular AF patients initiating anticoagulation from Oct 2010-Dec 2012 from a large US database of commercial and Medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
52
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 26 publications
8
52
2
1
Order By: Relevance
“…Warfarin inhibits vitamin K utilization, which reduces the activation of prothrombin complex proteins and the activity of clotting factors, effectively slowing thrombin generation and clot formation. [2][3][4] NOACs such as rivaroxaban and apixaban are specific inhibitors of factor Xa, and dabigatran is a direct thrombin inhibitor. [3][4][5] Reducing the risk of forming a clot increases hemorrhagic diathesis, [3][4][5] which increases the risk of intraocular hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Warfarin inhibits vitamin K utilization, which reduces the activation of prothrombin complex proteins and the activity of clotting factors, effectively slowing thrombin generation and clot formation. [2][3][4] NOACs such as rivaroxaban and apixaban are specific inhibitors of factor Xa, and dabigatran is a direct thrombin inhibitor. [3][4][5] Reducing the risk of forming a clot increases hemorrhagic diathesis, [3][4][5] which increases the risk of intraocular hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…1 The main advantage of NOACs compared with warfarin is the lack of coagulation monitoring or dosage adjustments required due to more predictable pharmacokinetic properties. [2][3][4] Recent studies have examined the risk of bleeding with these drugs, however, information on the risk of ocular bleeding with NOACs is scant.…”
Section: Introductionmentioning
confidence: 99%
“…In a cohort from the United States (2010-2012), 62% of patients with non-valvular atrial fibrillation (AF) were prescribed warfarin [1], and data from Europe (2013) showed a range of DOAC use between 0.3% (Italy) and 11.6% (Germany) [2] in the same patient group.…”
Section: Editorialmentioning
confidence: 99%
“…The use of novel anticoagulants (NOACs) has increased dramatically since its introduction with about 1/3 of patients with AF using them for stroke prophylaxis [17]. They represent a safe and efficacious alternative to warfarin.…”
Section: Role Of Novel Anticoagulantsmentioning
confidence: 99%